Primaquine-loaded transdermal patch for treating malaria: design, development, and characterization - Pankaj Sharma; Mukul Tailang (Future Journal of Pharmaceutical Sciences, 2022)
Abstract Background The goal of the current study was to create, improve, and test a transdermal patch loaded with primaquine for the treatment of malaria. Several ingredients were used to create the transdermal patch. For the choosing of polymers, placebo patches were created. The optimization of polymer ratios for patch development and testing their impact on tensile strength, in vitro drug release, in vitro drug permeation, and ex vivo drug permeation employed response surface methods. The F5 formulation was chosen as the optimal formulation based on these answers to the data. The stability of the F5 formulation was examined. According to the findings of trials on acute skin irritation, no place where transdermal patches were given showed any signs of clinical abnormalities or a change in body weight. No erythema or edema of the skin was seen in the rabbit’s skin. Results It was observed that tensile strength of the transdermal films formulated with Eudragit RL100 and hydroxypropyl methylcellulose (P mix) was found between 0.32 ± 0.017 and 0.59 ± 0.013 kg/cm2, which were 0.32 ± 0.017 (F1), 0.36 ± 0.012 (F2), 0.35 ± 0.015 (F3) for P mix ratio 1:1, 0.42 ± 0.011 (F4), 0.49 ± 0.010 (F5), 0.55 ± 0.016 (F6) for P mix ratio 1:2 and 0.56 ± 0.014 (F7), 0.57 ± 0.010 (F8), 0.59 ± 0.013 (F9) for P mix ratio 1:3. Data fitting to the Peppas, Hixon–Crowell, Higuchi, and Zero-order models was used to examine the optimized transdermal patch (F5) release kinetic mechanism. Data comparison was done using the correlation coefficient (R 2). Zero-order had an observed correlation coefficient (R 2) of 0.9988, which was greater than that for other models. Therefore, it was clear that the medication was released from the formulation after the Zero-order release. Conclusion The ideal thickness, percent elongation, and tensile strength of the primaquine therapeutic transdermal patches were prepared for transdermal delivery. The therapeutic transdermal patch was prepared by using Eudragit RL100: HPMC K15M (1:2) into the patch because this combination was responsible for the significant delivery of the drug into the bloodstream. The therapeutic transdermal patch has a notable penetration rate. Dimethyl sulfoxide was used as a permeation enhancer, which helped to obtain a high penetration rate. The statistical analysis was used to support the improved formulation. The therapeutic transdermal patch is a potential vehicle for the administration of primaquine, according to stability studies.